Education and its Political Context for the Marginalised A Study based on Ambedkar Nagar District - Patel, Divyanshu (JOURNAL OF INDIAN EDUCATION, 2016)
This research paper attempts to analyse the link between educational development and social mobility in deprived sections of the society. The basic thrust of the paper is to examine the multi-layered correlation between educational development and social and political mobility in society. A corollary to the same is an attempt at understanding how they affect each other. In this context, the central idea that this paper seeks to address and explore is the link that exists between education and social mobility, in light of a comparative framework built upon the ideas of Gandhi, Ambedkar and Lohia. For the same, the district of Ambedkar Nagar, situated in Uttar Pradesh (U.P.) has been chosen as a sample for the study. Data was collected from two schools, established with the cooperation of local people in the district, and interviews were conducted with people who actively participated in the social movements of the region.